083. Bilateral Mammae Reduction in Patients with Gestational Gigantomastia - Prasetya, I Made Maha; Setiawan, Gede Budhi (JBN (Jurnal Bedah Nasional); Vol 8 No 2 (2024): Proceeding The 2nd National Conference of Indonesia Surgical Education, 2024)
Background : Gestational gigantomastia is a rare clinical condition characterized by rapid and disproportionate breast enlargement during pregnancy. This case report describes a 24-year-old female patient with bilateral gigantomastia. Case: A 24-year-old female patient presented with complaints of a lump in both breasts that had progressively enlarged since her first pregnancy. Physical examination revealed breast enlargement measuring 30x20 cm, with signs of skin stretching, redness, no lesions, and engorged veins around both the left and right breasts. On palpation, there was no tenderness, the tissue felt soft, no masses were detected, and there was retraction of the nipple. In the right and left axillary regions, masses measuring 4x5 cm and 4x3 cm, respectively, were noted, matching the skin color. Breast ultrasound showed diffuse edematous changes in bilateral mammary parenchyma accompanied by duct ectasia, with a differential diagnosis of mastitis. The patient was diagnosed with bilateral gigantomastia and underwent reduction mammoplasty. Conclusion: This case report describes a patient with gestational gigantomastia who underwent reduction mammoplasty and excision of aberrant breast tissue.